The demand for air quality : a case study in Bogotá, Colombia (2015)
Using a (second stage) hedonic housing model, this paper identifies an inverse demand function for air quality in Bogota, the fourth most polluted city in Latin America (annual average of PM10 52 mg/m3). We use precipitation and distance to monitoring stations as instruments for pollution. We found that the monthly benefits of compliance with the U.S Environmental Pollution Agency standard (50 mg/m3 - annual average), and the far more stringent World Health Organization standard (20 mg/m3 - annual average) are U$7.12 and U$72.91per household respectively. Accordingly, these values represent about 1% and 8% of the average household income.